PRAGMATISM OF CUSTOMS REGULATION OF THE CONSUMER MARKET IN UKRAINE - HUTSUL, Inna; KRYSOVATA, Kateryna (Scientific journal «World of Finance», 2021)
Introduction. The customs regulation of the consumer market is one of the main universally recognized means of implementing state economic policy, a tool for fulfilling internal tasks. The main work in improving customs regulation of the consumer market should be aimed at increasing the competitiveness of domestic producers, promoting domestic and foreign investment for the national economy, as well as the development of new progressive and harmonized with European practice systems of product standardization and certification.The purpose of the article is to identify pragmatic aspects of customs and tariff regulation of the consumer market, systematization of vectors to increase the efficiency of state regulation of the consumer market of Ukraine.Methods. Methods of dialectical analysis and synthesis, as well as methods of logical generalization, comparison and formalization are used in the research.Results. The essence and social role of the consumer market are studied. Emphasis is placed on the need for state regulation of the consumer market using customs tools. It is established that the development of the consumer market is determined by changes in macroeconomic indicators, among which one of the key is retail trade. The share of the population's expenditures on the purchase of goods and services in the amount of total expenditures (revenues) was monitored. It is revealed that the main element of customs and tariff regulation of the consumer market of Ukraine is the customs tariff. Based on the results of the study of theoretical and practical principles of customs regulation of consumer Ukraine, measures were systematized that will improve the efficiency of its implementation, sustainable and progressive development.Prospects. Further research will focus on the implementation of innovative approaches to international customs regulation, in particular in the European Union, in national practice in order to improve the efficiency of the consumer market.